ANALYSIS OF SPORTS GAMES ACTIVITIES AT NIGHT AT GARUT UNIVERSITY AND SULTAN IDRIS EDUCATION UNIVERSITY - Yunaira Wiguna, Hazkia; Septianti, Lastri; Angga Permadi, Asep; Izwan Bin Shahril , Mohd; Akmal Hakim Bin Mohd Asri , Mohammad (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Purpose. The increasingly hectic activities of society cause a person's free time to rest and exercise is decreasing. This, of course, has a huge impact on one's health. Game sports activities at night are the remaining options for those who have a very busy schedule. Materials and Methods. The research method used an intrinsic case study method. A case study is research conducted on an object that is carried out in a complete, comprehensive, and in-depth manner using various data sources. The type of research conducted was from various sources such as field surveys, journals, books, the internet and other literature. Results. Game sports activities at night were a frequent activity to fill good leisure time for UNIGA and UPSI students after completing activities during the day, as well as relieving stress after learning activities, night sports can also help students to maintain and strengthen bonds or bonding with friends, build togetherness, and create very valuable memories. Conclusion. It can be concluded that there was no significant difference in evening activities between the two universities. There were various reasons for choosing to exercise at night, namely: busyness for some students.